Efectos deformantes de artritis reumatoidea, en adultos mayores, utilizando técnicas del factor reumatoide y anticuerpos antinucleares, estudio a realizarce; parroquia puerto pechiche, cantón Puebloviejo, provincia Los Ríos. abril – octubre 2014 - Cando Yumbulema, Marcos (2014)
This research is aimed at strengthening the role that licensed clinical laboratory for the diagnosis of patients with disfiguring effects of rheumatoid arthritis, and its incidence in older adults, using techniques of rheumatoid factor and antinuclear antibodies, as a student of the faculty of health; why our research has a focus from the prevention and treatment remain a very important research into the pathological pillar. The design of this research is descriptive and field. The sample was made with elderly patients who had deforming effects due to rheumatoid arthritis. The questionnaire was based on questions to determine the patient, prevention, complications, treatment, mainly the diagnosis to be performed by your doctor confidence through the use of laboratory tests carried out by professionals in this branch of medical science in the case clinical laboratory in question. The result is having achieved impart new techniques of care and prevention and diagnosis through the use of techniques of rheumatoid factor and antinuclear antibodies so that patients avoid future complications.